Sistem Komunikasi Jarak Jauh Alat Pengukur Kecepatan Dan Arah Angin Berbasis Mikrokontroller - Yudhi Yudhi; Jamalludin Jamalludin (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
Monitoring wind speed and direction is usually performed at close range, therefore,it is necessaryto monitor remotely for time efficiencies. Making these systems start with a literature study the data relating to the technology to be used. Then the data was processed to determine the design of the system being designed. Making this system begins with a measuring instrument wind speed and wind direction. In this device for chopping round of the wind speed sensor using optocoupler. And magnetic hall sensor, constructed as a weathervane as a determinant of the wind direction sensor. RTC is used as time refference of measurement. Arduino Mega 2560 Microcontroller used to process data obtained from sensors and RTC. Then the data is the data is recorded with a cycle which can be set. After the manufacture of measuring devices and then proceed to make the data transmission system and application interface. With GSM shield Sim900a data that has been recorded is sent in the form of SMS through GSM network. Then the data is received by GSM shield servers and read by Arduino UNO. Data is read by Arduino UNO is then sent to a computer with serial communication. The data is sent to the computer will be processed by the application interface to be stored and displayed. The results of this system is able to measure and store data speed and direction of the wind from a distance. With a windspeed error of 4.56% of the measurements manually, and wind direction indicates the actual wind direction.